Hybrid adaptive sine cosine algorithm with finite-time prescribed performance PID control for pneumatic servo systems - Addie Irawan, Hashim; Mohd Helmi, Suid; Raja Mohd Taufika, Raja Ismail; Ahmad Nor Kasruddin, Nasir; M. F. M., Jusof; Mohd Iskandar Putra, Azahar (Elservier, Science Direct, 2025)
This paper addresses the challenge of enhancing pressure regulation in pneumatic servo systems, specifically for proportional valve-controlled double-acting pneumatic cylinders (PPVDC). A Hybrid Nonlinear Sine Cosine Algorithm (HNSCA) is proposed to optimize a Finite-Time Prescribed Performance Control (FT-PPC) integrated with a PID controller. The HNSCA combines the Nonlinear Sine Cosine Algorithm (NSCA) with Adaptive Safe Experimentation Dynamics (ASED) to fine-tune FT-PPC-PID parameters, achieving rapid transient response and system stability. Simulation results demonstrate significant improvements over other optimization variants like ESCA and ASCA, including a 96% faster rise time, 61.9% reduction in settling time, and 6.4% lower overshoot. Additionally, HNSCA reduced pressure oscillations by 25%–30%, lowered power consumption by 20%–30%, and achieved up to a 50% reduction in energy consumption under a 10 kg load. It also enhanced subsonic flow stability by 10%–15% under choked flow conditions. These advancements offer practical benefits for industries utilizing pneumatic systems, such as manufacturing and robotics, by providing more precise control, reducing energy costs, and extending equipment lifespan. The findings highlight the effectiveness of the proposed approach in error minimization and long-term stability for pneumatic servo systems.